A Commercially Available Thermogenic Dietary Supplement Increases Resting Metabolic Rate in Physically Active Males: A Randomized, Double-Blind, Placebo-Controlled Investigation. (3rd March 2020) - Campbell, Bill I.; Perry, Ross; Horsley, John; Aguilar, Danielle; Shimshock, Taylor; Fox, Carl; Vargas, Andres; Colenso-Semple, Lauren
Abstract: Males seeking to improve body composition may ingest thermogenic dietary supplements with the goal of elevating resting metabolic rate. The purpose of this study was to examine the effects of a commercially available dietary supplement (containing ingredients that promote thermogenesis) on resting metabolic rate (RMR) in a randomized, double-blind, placebo-controlled cross-over study. Ten healthy, physically active males (age: 26.5 ± 6.4 years; height: 177.6 ± 7.2 cm; body weight: 80.5 ± 10.8 kg) underwent two testing sessions separated by approximately 7 days. Following baseline assessments of RMR, heart rate (HR), and blood pressure (BP), each participant ingested a thermogenic dietary supplement or a placebo. Assessments were repeated at 60, 120, and 180 minutes postingestion. Approximately 1 week later, participants ingested the alternative supplement and the assessments were repeated. Post hoc analyses revealed that the dietary supplement treatment demonstrated significant elevations in RMR during the postingestion period ( p < 0.05) from 1, 859 ± 266 kcal to 2, 027 ± 288 kcal (increase of 9%) to 2, 072 ± 292 kcal (increase of 11.5%) and to 2, 040 ± 271 kcal (increase of 9.7%) at 60, 120, and 180 minutes postingestion, respectfully. No significant elevations were observed in the placebo treatment at any time point. HR and BP measures were within normal clinical values throughout the intervention.